The Economic Effects of the Protestant Reformation: Testing the Weber Hypothesis in the German Lands - Davide Cantoni (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2013)
Following Max Weber, many theories have hypothesized that Protestantism should have favored economic development. With its religious heterogeneity, the Holy Roman Empire presents an ideal testing ground for this hypothesis. Using population figures of 272 cities in the years 1300–1900, I find no effects of Protestantism on economic growth. The finding is precisely estimated, robust to the inclusion of various controls, and does not depend on data selection or small sample size. Protestantism has no effect when interacted with other likely determinants of economic development. Instrumental variables estimates, considering the potential endogeneity of religious choice, are similar to the OLS results.
urn:nbn:de:bvb:19-epub-14811-9
Keywords: N13; N33; O11; Z12; 330; Protestantism; Culture; Economic Growth; Historical Development; Germany; Stadt; Protestantismus; Kulturgeschichte; Wirtschaftswachstum; Wirtschaftsgeschichte; Deutschland (bis 1945)